Students’ Difficulties in Learning Tenses by Grammar Translation Method at Star English Course Parepare - Raudah Umar, Ghefira; Asiza, Nur; Zulfah, Zulfah; Noviasmy, Yessicka (Jurnal Pedagogi dan Inovasi Pendidikan, 2025)
Grammar Translation Method (GTM) is a language learning method that focuses on understanding grammar and translating texts from a foreign language to the mother tongue, and vice versa. This study aims to determine the effectiveness of the Grammar Translation Method in teaching grammar concepts, especially tenses, in EFL (English as a Foreign Language) classes, especially at Star English Course Parepare. The research method used is quantitative survey. The samples of this research were students from Level 4 (Advance 1 and Advance 2) Star English Course Parepare. In this research, the researcher used total sampling techniques and took 70 students as sample. The data collection technique used a questionnaire with hypothesis testing carried out by using simple linear regression analysis using the SPSS 25 program. The results of the research show that Grammar Translation Method has a significant influence on students' difficulties in learning tenses. Seen from the Tcount value of 9,755 > T-table 1,995 with a significance of 0,007 < 0,05. Statistical test results show that Grammar Translation Method has a positive and significant impact on students' learning difficulties. And psychological factor is the most influential aspects of students’ difficulties in learning tenses through Grammar Translation Method. Fear of making mistakes, lack of confidence, and linguistic anxiety are the main obstacles in the learning process. Therefore, there is a need for a more varied, communicative, and student-centered approach in learning Tenses.